The limitations of policy coordination in the euro area under the European Semester - Zsolt M. Darvas; Álvaro Leandro (Bruegel, 2015)
The European Semester is a yearly process of the European Union to improve economic policy coordination and ensure the implementation of the EU's economic rules. Each Semester concludes with recommendations for the euro area as a whole and for each EU member state. We show that implementation of recommendations was poor at the beginning of the Semester in 2011, and has deteriorated since. The European Semester is not particularly effective at enforcing even the EU's fiscal and macroeconomic imbalance rules. We find that euro-area recommendations with tangible economic goals are not well reflected in the recommendations issued to member states. Finally, we review various proposals to improve the efficiency of the European Semester and conclude that while certain steps could be helpful, policy coordination will likely continue to have major limitations.
Keywords: 330